Securitization of Memory: a Theoretical Framework to Study the Latvian Case - Pakhomenko, Sergii; Sarajeva, Olga (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The article suggests and argues a theoretical framework for studying a particular case of memory securitization. It is based on the constructivist perception of security that is systematically framed in the studies of representatives of the Copenhagen School, who consider security as a socially constructed phenomenon and define identity protection to be one of its primary goals. Pursuant to this approach, the article presents a correlation between memory and security in at least three aspects. In the first instance, similar to security, collective memory is socially determined. In the second instance, collective memory lies at the core of various forms of identity, including national identity. In the third instance, collective memory is not only an object of protection but also a resource, which is used by securitization actors for threat identification, enemy image modeling as well as for defining the means of protection. The Latvian case is applied for setting the theoretical framework of the memory securitization model. In future, it might be used to study specific juridical and political mechanisms of memory securitization in the countries of Central and Eastern Europe. The authors perceive the securitization of memory as a diverse complex of measures aimed at establishing and setting a certain historical narrative, as well as convincing society to be actively loyal to it. Accordingly, the policy of memory is defined as a mechanism for putting securitization in practice. The initial conditions for understanding this process in Latvia are the post-communist transition, ethnocultural divisions of the society, and the external factor represented by Russia, that promotes its historical narratives. In one respect, R. Brubaker’s concept of the “nationalized” state is taken as a theoretical model of the politics of memory in Latvia. According to this concept, the official narrative of post-communist countries has been set as a nation-oriented one. On the other hand, the concept of the memory regime developed by M. Bernhard and J. Kubik is also considered. As per their theory, the memory regime in Latvia can be described as being divided into the official and alternative narrative of counter-memory, which is based on the Soviet legacy.

Artykuł proponuje i uzasadnia teoretyczne ramy badania sekurytyzacji pamięci na konkretnym przypadku. Opiera się na konstruktywistycznym postrzeganiu bezpieczeństwa, systematycznie formułowanym w badaniach przedstawicieli Szkoły Kopenhaskiej, którzy traktują bezpieczeństwo jako zjawisko konstruowane społecznie, uznając ochronę tożsamości za jeden z głównych jego celów. Zgodnie z tym podejściem artykuł przedstawia korelację między pamięcią a bezpieczeństwem w co najmniej trzech aspektach. W pierwszej kolejności, podobnie jak w przypadku bezpieczeństwa, pamięć zbiorowa jest zdeterminowana społecznie. Po drugie, pamięć zbiorowa leży u podstaw różnych form tożsamości, w tym tożsamości narodowej. Po trzecie, pamięć zbiorowa jest nie tylko przedmiotem ochrony, ale także zasobem, który jest wykorzystywany przez podmioty sekurytyzacyjne do identyfikacji zagrożeń, modelowania obrazu wroga, a także do definiowania środków ochrony. Teoretyczne ramy modelu sekurytyzacji pamięci ustalono w oparciu o przypadek łotewski. W przyszłości może on posłużyć do badania konkretnych prawnych i politycznych mechanizmów sekurytyzacji pamięci w krajach Europy Środkowo-Wschodniej. Autorzy postrzegają sekurytyzację pamięci jako zespół różnorodnych środków mających na celu ustanowienie i ustalenie pewnej narracji historycznej, a także przekonanie społeczeństwa do aktywnej lojalności wobec tej narracji. W związku z tym polityka pamięci jest definiowana jako mechanizm wprowadzania sekurytyzacji w praktyce. Warunki wstępne dla zrozumienia tego procesu na Łotwie obejmują transformację postkomunistyczną, podziały etniczno-kulturowe społeczeństwa oraz czynnik zewnętrzny, jakim jest promująca swoje narracje historyczne Rosja. W jednym aspekcie teoretyczny model polityki pamięci na Łotwie odnosi się do koncepcji „unarodowionego” państwa R. Brubakera. Zgodnie z tą koncepcją oficjalna narracja krajów postkomunistycznych została określona jako narodowa. Z drugiej strony rozważono także koncepcję reżimu pamięci, opracowaną przez M. Bernharda i J. Kubika. Zgodnie z ich teorią reżim pamięci na Łotwie można opisać jako podzielony na oficjalną i alternatywną narrację kontrpamięci opartej na dziedzictwie sowieckim.
Sekurytyzacja pamięci: teoretyczne ramy badania przypadku łotewskiego
Keywords: security; securitization; identity; historical memory; politics of memory; Latvia; narrative; memory regime; security dilemma; bezpieczeństwo; sekurytyzacja; tożsamość; pamięć historyczna; polityka pamięci; Łotwa; narracja; reżim pamięci; dylemat bezpieczeństwa